Examining Social Exchange Theory and Social Change in the Works of George Caspar Homans – Implications for the State and Global Inequalities in the World Economic Order - Ogbonna, Hyginus Obinna; Mbah, Chidi Slessor (Richtmann Publishing, 2022)
This paper focuses on the critical investigation of ‘Social Exchange theory’ and ‘Social Change’ in the works of George Homans. The objectives are to appropriate the interpenetrations of the twin concepts, and their implications towards the amelioration of the human condition both within the state, and within the global socio-economic relations. Thus, the paper achieves its objectives by applying a qualitative-critical descriptive method of analysis on the subject matter –with a critique from Peter Blau’s variant perspective for helpful extrapolations to explaining human condition within the state, and globally. The paper made some findings, draws conclusions, and recommendations. A few of these findings include 1) the propensities of breaching the norm of reciprocity in social exchange process are higher than the tendencies to maintain the norm; 2) at the breach of the norm of reciprocity, there are higher risks of losses than the gains, and there are immanent implications; 3).That societal progress can also emerge via resistance to an ‘apopular’ status quo. The paper concluded that, there is a semblance of order when the norm of reciprocity is observed among nations, and within nations; but moments of aggression exists with immanent crisis-tendencies that are anti-development where the norm is violated. Therefore, the paper recommends: the state should be committed to its part of the social contract with the citizenry in terms of provisions of human-centered development facilities; and where the state loses the sanctity of its legitimacy and turns to a ‘class-state’, counter-reactions and resistance from the subaltern classes (the civil society) through protests for progressive social change or for the improvement of the human condition, should not be discouraged. Additionally, the advanced nations should recognize the socioeconomic rights of the less developed nations for a fair deal in the global economic relations. Received: 29 November 2021 / Accepted: 28 December 2021 / Published: 5 January 2022